A study on the corporate culture of Dianping - Feng-Ping Wei; 최명철; Xian-Fa Shang (International Journal of Advanced Culture Technology(IJACT), 2019)
In recent years, with the development of IT technology and mobile communication, the powerful communication function of the Internet will gradually eliminate the information asymmetry between supply and demand, and the third-party review website emerges as The Times require. Dianping.com was founded in 2003. After a few years of development, it has become an independent third-party consumer review website worldwide. One of the reasons for such great success is corporate culture, which plays an important role in human resource management. The competition of enterprises is not only the competition of products and cost advantages, but also the superior enterprise culture presented to customers in the international environment. The competition between third-party review sites has been very fierce. In just a few years, many foreign thirdparty review websites went public and made profits, but some domestic start-ups went bankrupt due to the lack of a good business model and corporate culture. A good business model is particularly important. Taking dianping.com as the research object and combining with the business model of the company, this paper studies the unique corporate culture of dianping.com, hoping to help the company through the investigation and research of this paper, so as to improve the company in the future. And put forward a certain practical significance and value.